Analysis Of Discretionary Accrual, Differences In Profits, Cash Flow And Fiscal Profits On Profits Persistence Of National Manufacturing Companies Listed In Indonesian Stock Exchange - Rika Lidyah; Maya Indriani Yacob Impak; Dede Rustaman; Loso Judijanto; Musran Munizu (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This study examines the effects of cash flow, discretionary accruals, and accounting profit on the persistence of profits in manufacturing enterprises. Manufacturing firms registered on the Indonesian Stock Exchange make up the study's population. Purposive sampling was the technique employed for sample selection. Secondary data, specifically financial reports of manufacturing firms that have gone public and are listed on the IDX, is the type and source of data used in this study. Descriptive statistics and multiple regression are the statistical techniques used to examine data and test hypotheses. Profit persistence is significantly harmed by the discrepancy between accounting profit and fiscal profit, which serves as a stand-in for deferred tax expense. Earnings permanence is significantly harmed by discretionary accrual. Profit persistence is significantly influenced favorably by operating cash flow. We can draw the conclusion that a company's earnings will last longer the higher its operating cash flow.